2019
DOI: 10.1002/htj.21601
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on pyramid solar still with single and double collector cover—Comparative study

Abstract: Sun radiation is the heat energy source for solar still.That should be utilized maximum for increasing the evaporative rate at the top surface of the brine. The pyramid shape solar still (PSSS) can receive solar input radiation from all four directions. In this research, the top layer of conventional pyramid shape solar still (CPSSS) is covered with air-packed cover and analysed the effect in the modified still after air packed in between the two glasses, finally, that result is compared with the CPSSS. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The variations of water temperature every hour during all the testings are plotted in Figure 4. It is observed that water temperature increases linearly with the increase in the solar intensity; it reaches its maximum value when the solar intensity is maximum, and it is found to be decreased during the sunset hours 29‐43 . The maximum hourly water temperature for the CSS, the CSSGC, the CSSBH, and the CSSGCBH is found as 61°C, 59°C, 67°C, and 65°C, respectively.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The variations of water temperature every hour during all the testings are plotted in Figure 4. It is observed that water temperature increases linearly with the increase in the solar intensity; it reaches its maximum value when the solar intensity is maximum, and it is found to be decreased during the sunset hours 29‐43 . The maximum hourly water temperature for the CSS, the CSSGC, the CSSBH, and the CSSGCBH is found as 61°C, 59°C, 67°C, and 65°C, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…It is observed that water temperature increases linearly with the increase in the solar intensity; it reaches its maximum value when the solar intensity is maximum, and it is found to be decreased during the sunset hours. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] The maximum hourly water temperature for the CSS, the CSSGC, the CSSBH, and the CSSGCBH is found as 61°C, 59°C, 67°C, and 65°C, respectively. The hourly water temperature is maximum for the CSSBH and minimum for the CSSGC.…”
Section: Variations Of Water and Collector Cover Temperaturementioning
confidence: 95%
“…Kumar et al [63] are interested to study the pyramid shape of the solar still, which receives the solar radiation from four directions. They experimentally investigated the effect of the air-packed cover in the conventional pyramid solar still, located on its top.…”
Section: Energy Analysismentioning
confidence: 99%
“…Kumar et al [15] used a double collector cover in the PSS. Their results exhibited that double collector cover reduces the thermal efficiency of the PSS as the air gap between the collector cover increased the cover temperature.…”
Section: Introductionmentioning
confidence: 99%